Disordered amorphous calcium carbonate from direct precipitation - Farhadi Khouzani, M.; Chevrier, D.; Güttlein, P.; Hauser, K.; Zhang, P.; Hedin, N.; Gebauer, Denis (The Royal Society of Chemistry, 2015)
© The Royal Society of Chemistry.Amorphous calcium carbonate (ACC) is known to play a prominent role in biomineralization. Different studies on the structure of biogenic ACCs have illustrated that they can have distinct short-range orders. However, the origin of so-called proto-structures in synthetic and additive-free ACCs is not well understood. In the current work, ACC has been synthesised in iso-propanolic media by direct precipitation from ionic precursors, and analysed utilising a range of different techniques. The data suggest that this additive-free type of ACC does not resemble clear proto-structural motifs relating to any crystalline polymorph. This can be explained by the undefined pH value in iso-propanolic media, and the virtually instantaneous precipitation. Altogether, this work suggests that aqueous systems and pathways involving pre-nucleation clusters are required for the generation of clear proto-structural features in ACC. Experiments on the ACC-to-crystalline transformation in solution with and without ethanol highlight that polymorph selection is under kinetic control, while the presence of ethanol can control dissolution re-crystallisation pathways.